2006
DOI: 10.1590/s1516-89132006000100003
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenetic response of cotyledon and leaf explants of melon (Cucumis melo L.) cv. Amarillo Oro

Abstract: Callus cultures from cotyledon and leaf explants of a Spanish cultivar of melon (Amarillo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Additionally, different plant genotype and varieties exhibit quite different regeneration rates (18). Explant age and gelling agents may also affect the melon regeneration efficiency (19).…”
Section: Effects Of Ba and Cefotaxime On Shoot Regeneration And Callumentioning
confidence: 99%
“…Additionally, different plant genotype and varieties exhibit quite different regeneration rates (18). Explant age and gelling agents may also affect the melon regeneration efficiency (19).…”
Section: Effects Of Ba and Cefotaxime On Shoot Regeneration And Callumentioning
confidence: 99%
“…Six regeneration media, RM1 (Ficcadenti and Rotino 1995), RM2 (Guis et al 2000), RM3 (Yadav et al 1996), RM4 (Fang and Grumet 1990), RM5 (Souza et al 2006), and RM6 (Bordas et al 1997), were evaluated with our melon genotypes (Table 1). Each medium represented the optimal composition to give the highest regeneration frequency in each study reported.…”
Section: Shoot and Root Regenerationmentioning
confidence: 99%
“…The synthetic auxin 2,4-dichlorophenoxyacetic acid has been widely used to induce somatic embryogenesis (AkasakaKennedy et al 2004;Gray et al 1993;Guis et al 1997;Kintzios et al 2004;Kintzios and Taravira 1997;Oridate and Oosawa 1986). In addition, 6-(c,c-dimethylallylamino)-purine (2iP), gibberellic acid (GA 3 ), kinetin, thidiazuron and a-naphthaleneacetic acid have been used in melon culture (Fang and Grumet 1990;Ficcadenti and Rotino 1995;Guis et al 2000;Souza et al 2006;Yadav et al 1996). The effects of these growth regulators on melon regeneration differed depending on plant genotype, explant type and culture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To date propagation of Cucumis melo has been reported by different research groups [34,36,48,49,50,51]. The main differences between the present study and the earlier ones are the growth regulators used and melon cultivars selected.…”
Section: In Vitro Plant Regenerationmentioning
confidence: 75%
“…The main differences between the present study and the earlier ones are the growth regulators used and melon cultivars selected. We used Hasanbey and Cinikiz melon cultivars as explants; while the others used 'Amarillo oro' [48,51], 'Accent', 'Galia', 'Presto', and 'Viva' [36], 'Revigal' and 'Kirkagac' [34,50], 'Topmark' [49,50]. After three weeks on a MS medium free from plant growth regulator, approximately 80% of cotyledon explants gave rise to friable callus ( Figure 5).…”
Section: In Vitro Plant Regenerationmentioning
confidence: 99%